A Hybrid Formulation between Differential Evolution and Simulated Annealing Algorithms for Optimal Reactive Power Dispatch - Farida Laouafi; Ahcene Boukadoum; Salah Leulmi (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2018)
The aim of this paper is to solve the optimal reactive power dispatch (ORPD) problem. Metaheuristic algorithms have been extensively used to solve optimization problems in a reasonable time without requiring in-depth knowledge of the treated problem. The performance of a metaheuristic requires a compromise between exploitation and exploration of the search space. However, it is rarely to have the two characteristics in the same search method, where the current emergence of hybrid methods. This paper presents a hybrid formulation between two different metaheuristics: differential evolution (based on a population of solution) and simulated annealing (based on a unique solution) to solve ORPD. The first one is characterized with the high capacity of exploration, while the second has a good exploitation of the search space. For the control variables, a mixed representation (continuous/discrete), is proposed. The robustness of the method is tested on the IEEE 30 bus test system.